1983
DOI: 10.1111/j.1540-4560.1983.tb00128.x
|View full text |Cite
|
Sign up to set email alerts
|

The Threat of Nuclear War: Risk Interpretation and Behavioral Response

Abstract: This study examines the psychological antecedents of behavioral responses to the threat of nuclear war. Two groups known to have responded behaviorally to the threat of nuclear war-nuclear freeze activists and survivalists-are compared to a sample of members of the general public. The influence of four types of psychological antecedents was explored. The antecedents studied were: judgments of risk, efficacy judgments, attributions of causality and moral responsibility, and general political orientations. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
78
1

Year Published

1986
1986
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 13 publications
5
78
1
Order By: Relevance
“…the sense that the individual citizen can have an impact on the political process. For example, Fiske (1987) argues that, "The antinuclear activist believes that nuclear war is preventable, not inevitable, and that citizens working together can influence government action to decrease the chance of a nuclear war" (p. 213; see also Hamilton ef aL, 1987; Locatelli & Holt, 1986;Tyler & McGraw, 1983;Wolf, Gregory & Stephan, 1986). It is argued that the activist's specific sense of "nuclear efficacy" is linked to a broad sense of personal (rather than external) control over life events in general (locus of control; Rotter, 1966) which leads him or her to become involved in other types of political activity as well (but see Levenson, 1981).…”
Section: Perceiving Social Change As Possiblementioning
confidence: 97%
“…the sense that the individual citizen can have an impact on the political process. For example, Fiske (1987) argues that, "The antinuclear activist believes that nuclear war is preventable, not inevitable, and that citizens working together can influence government action to decrease the chance of a nuclear war" (p. 213; see also Hamilton ef aL, 1987; Locatelli & Holt, 1986;Tyler & McGraw, 1983;Wolf, Gregory & Stephan, 1986). It is argued that the activist's specific sense of "nuclear efficacy" is linked to a broad sense of personal (rather than external) control over life events in general (locus of control; Rotter, 1966) which leads him or her to become involved in other types of political activity as well (but see Levenson, 1981).…”
Section: Perceiving Social Change As Possiblementioning
confidence: 97%
“…Evidence for the effects of certainty on attitude-behavior consistency is available in Tyler and McGraw's (1983) research on antinuclear activists. In a survey of citizen participation in antinuclear activities, the researchers found that the activists were much more certain than nonactivists that a nuclear war would occur.…”
Section: Certaintymentioning
confidence: 98%
“…If, for example, individuals believe that they are more concerned than others about the environment, or if they believe that they already do more than other people do, they may decide not to take further actions to protect the environment. This possibility is particularly likely given the fact that environmentalism and other forms of activism are pogitively associated with a personal sense of responsi bility (Hines, Hungerford, & Tomera, 1986;Tyler & McGraw, 1983). To date, however, no researchers have suggested that self-enhancement biases in social concern may serve to impede activism.…”
mentioning
confidence: 94%